3D bioprinted models of Glioblastoma - Leslie, Nick (Neuro Oncol, 2018)
In-vitro brain tumour models are valuable tools both to study cancer biology and for successful pre-clinical testing of anticancer drugs. However, substantial challenges remain before we can create pathologically-relevant models which closely mimic the microenvironment of human brain tumours, their growth characteristics and their response to therapies. We have developed a 3D bioprinting strategy using modified alginate matrices incorporating hyaluronan and collagen, in order to create tumour-like structures containing both glioma stem cell lines and glioma derived stromal cells. Our results to date show that the printing process can be performed with minimal effects on cell viability, even when cells are printed at high density; that cells proliferate within the gel and that rapid cell-cell adhesion can be promoted with appropriate matrices. We are able to print glioma stem cells with and without stromal cells in separate layers within tumour like 3D constructs with a smallest feature size (resolution) of approximately 300 micrometers. This capability to spatially position cell populations and other components within a 3D tumour construct allows new experimental approaches by controlling individual parameters of the tumour microenvironment and should provide novel highly-reproducible models for preclinical drug testing.